RNA editing of interleukin-12 receptor beta2, 2451 C-to-U (Ala 604 Val) conversion, associated with atopy - Kondo, N; Matsui, E; Kaneko, H; Aoki, M; Kato, Z; Fukao, T; Kasahara, K; Morimoto, N (Clinical and experimental allergy, 2004)
The production of IgE in B lymphocytes is down-regulated by IFN-gamma. IL-12 induces IFN-gamma production by T lymphocytes and natural killer cells by binding to its specific receptor. RNA editing is a post-transcriptional modification. Here we show that the RNA editing of IL-12 receptor (R) beta2 is associated with atopy. Atopic patients and non-atopic healthy controls were studied. Fragments of IL-12R beta2 cDNA and genomic DNA were amplified and sequenced. Furthermore, the function of the IL-12R beta2 chain was investigated. Sequence analysis of the cDNA clones representing IL-12R beta2 mRNA transcripts revealed a C-to-U conversion at nucleotide 2451 (Ala 604 Val) on exon 13 in some atopic patients. Surprisingly, sequence analysis of their genomic DNA showed no 2451 C-to-T (Ala 604 Val) mutation. We concluded that the observed C-to-U mismatch in the cDNA clone is due to a post-transcriptional modification, RNA editing. The C-to-U conversion was observed in 21 (20.6%) of 102 atopic patients, whereas this conversion was observed in only 4 (3.8%) of 104 non-atopic subjects (P<0.001). IFN-gamma production by peripheral blood mononuclear cells (PBMCs) stimulated with IL-12 in the subjects with the C-to-U conversion was significantly lower than that in the subjects without the C-to-U conversion. In atopic patients with the C-to-U conversion, PBMCs faintly showed the tyrosine phosphorylation of Stat4, and the IgE production by PBMCs was not suppressed by IL-12 whereas it was suppressed by IFN-gamma. The RNA editing of IL-12R beta2, 2451 C-to-U (Ala 604 Val) conversion causes impairment of the IL-12 signal cascade and the subsequent reduction in IFN-gamma production, resulting in the impaired down-regulation of IgE production. This is the first report indicating that atopy is associated with RNA editing.